Solving Fractions by Applying the Bar Model Concept with the Butterfly Method - Jessica Low; Masitah Shahrill; Nordiana Zakir (Universitas Sriwijaya, 2020)
This study aims to investigate an intervention in the application of the Butterfly Method Algorithm with the Bar Model Concept on the addition and subtractions of Fractions to Year 9 students in one of the Government secondary schools in Brunei Darussalam. The Butterfly Method is an alternative visual method for teaching fractions where the diagonal and horizontal multiplication of the denominators and numerators are employed by drawing the Butterfly. A mixed-method approach was used to explore the impact of the intervention with data gathered from the students’ written pre- and post-tests and interview transcripts. The tests conducted before and after the intervention were used to analyze students’ errors and misconceptions. The students’ written analyses of the post-test results revealed that not all of the students applied the Butterfly Method. A few students were selected for interviews in order to gain deeper insights into how they developed the errors and misconceptions from both tests. Findings from the students’ interview transcripts revealed they were not confident with the Butterfly Method, and they needed more time to be familiar with the concept. Another factor for not applying the Butterfly Method is due to students’ confusion on subtracting fractions that has the same denominators as well as subtracting a proper fraction from a whole number. This study concluded that students who applied the Butterfly Method helped them to remember the new method from the intervention satisfactorily in comparison to those who lack the confidence in applying it.